Sleep Quality as a Predictor of Depression in Preclinical Medical Students - Auriza Nabila Atiqah; Ariesta Dewi Ciptorini; Haifa Hasna Putri; Reynhard Alfado Randalabi; Tedy Nurnizam (Riviera Publishing, 2026)
Sleep quality has emerged as a critical determinant of mental health among medical students worldwide. Poor sleep patterns are frequently associated with increased depressive symptoms, particularly in preclinical medical students who face intense academic pressure and limited recovery time. This study aims to examine the relationship between sleep quality and depression and to analyze its psychological implications among preclinical medical students. A literature review approach was employed using articles indexed in PubMed, Scopus, and ScienceDirect published between 2022 and 2026. A total of 13 eligible studies were analyzed based on predefined inclusion criteria focusing on validated instruments such as the Pittsburgh Sleep Quality Index (PSQI) and Patient Health Questionnaire-9 (PHQ-9). The results indicate a consistent and significant association between poor sleep quality and higher levels of depression, with odds ratios ranging from 1.50 to 3.99 across studies. Psychological factors such as anxiety and academic stress were identified as major mediators in this relationship, while behavioral factors such as screen time further exacerbated sleep disturbances. The discussion highlights that sleep quality is not merely a symptom but a significant predictive factor of depression in this population. In conclusion, poor sleep quality significantly increases the risk of depression among preclinical medical students, emphasizing the need for early screening, sleep hygiene interventions, and institutional mental health support programs.